Computer-aided cancer detection and diagnosis recent advances - Tang, Jinshan; Agaian, S. S. 1946- (SPIE Press, 2014)
Accurate imaging of cancerous tissue is a critical step in the fight to lower cancer mortality rates, and computer-aided detection and diagnosis (CAD) technologies play a key role. Over the last three decades, the field of diagnostic cancer imaging has witnessed a remarkable evolution that has affected virtually every aspect of research and clinical management of cancer. This book discusses recent high-quality research in key technologies used in CAD systems; the 11 chapters cover different types of cancers (including skin, breast, prostate, and colon cancer) and different scientific fields (such as biomedicine, imaging, image processing, pattern recognition, and system analysis) to further the major goals of current cancer imaging: provide more reliable disease characterization through the synthesis of anatomic, functional, and molecular imaging information; refine and optimize imaging capabilities in oncology; establish new imaging modalities and findings, and discover the potential use of these techniques; find more individualized assessment of tumor biology, personalized treatments, and response to treatment; develop image-processing-based cancer control systems; and explore imaging capabilities and strategies to streamline cancer drug development